Kvalitativno raziskovanje medvrstniškega nasilja: izhodišča in utemeljitev (Celostni pristop k medvrstniškemu nasilju: Psihosocialni konteksti in raziskovalne strategije, 2025)
Peer violence occurs in a social context, so it is essential to study this phenomenon in the very environment in which it occurs. This chapter presents part of the results of a qualitative study that was created as part of the project Social context as a factor of peer violence: how to contribute to an inclusive school by creating a positive peer culture?. Its purpose was to examine the views of students, teachers and guidance workers on the materials that were created as part of the project and are intended to prevent and respond to peer violence, and at the same time to explore their broader view of this topic. 19 students, 20 teachers and six guidance workers participated in the focus groups. The thematic analysis of the collected data showed that the participants perceive the presented materials as meaningful and important. They recognize the importance of social-emotional learning, especially strengthening relational competences, in preventing violence. The collected results indicate the importance of all employees working together to establish a school culture that strives for a safe and stimulating learning environment and responds appropriately to peer violence.